2004
DOI: 10.1080/03009740410005467
|View full text |Cite
|
Sign up to set email alerts
|

Rapid alleviation of signs and symptoms of rheumatoid arthritis with intravenous or subcutaneous administration of adalimumab in combination with methotrexate

Abstract: Either i.v. or s.c. adalimumab added to MTX significantly improved the signs and symptoms of RA compared with MTX alone. Subcutaneously administered adalimumab appeared to provide a response that was as great, as rapid, and as enduring as that with i.v. adalimumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 10 publications
1
15
0
1
Order By: Relevance
“…The efficacy of these biologicals has been evaluated in clinical trials using classical clinical outcome measures such as ACR20, HAQ, X-ray scores and DAS28 [1, 2]. Incorporating outcome measures such as DAS scores, imaging, as well as an evaluation of the patient’s quality of life has changed treatment targets in clinical practice and improved patient outcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of these biologicals has been evaluated in clinical trials using classical clinical outcome measures such as ACR20, HAQ, X-ray scores and DAS28 [1, 2]. Incorporating outcome measures such as DAS scores, imaging, as well as an evaluation of the patient’s quality of life has changed treatment targets in clinical practice and improved patient outcome.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, several studies have investigated the efficacy and safety of different biological therapies available in either IV or SC formula (eg. abatacept, golimumab, adalimumab, tocilizumab) and found no difference between these modes of administration [2, 46]. …”
Section: Introductionmentioning
confidence: 99%
“…Controlled trials have shown that adalimumab is safe and effective for treating rheumatoid arthritis, psoriatic arthritis, psoriasis, and ankylosing spondylitis. [18][19][20][21][22][23][24][25] Adalimumab is approved by multiple regulatory authorities for the treatment of rheumatoid arthritis, psoriatic arthritis, and ankylosing spondylitis. Adalimumab was approved in the United States in February 2007 for the treatment of moderate to severe Crohn's disease.…”
mentioning
confidence: 99%
“…Several clinical trials of RA patients demonstrated clinical and radiographic efficacy and safety of adalimumab in combination with standard antirheumatic therapy, including MTX 9,10,12,13,14,15,16 , and as monotherapy 17 . In a randomized controlled study of patients with established RA who had an inadequate response to initial treatment with MTX (DE019), adalimumab plus MTX was significantly more effective than MTX alone in reducing clinical signs and symptoms, improving physical function, and inhibiting radio graphic disease progression 9 .…”
mentioning
confidence: 99%